The Mechanism of Dross Formation on Aluminium and Aluminium Magnesium Alloys - Impey, Susan A. (Cranfield University, 1989)
Metal loss is an unavoidable consequence of the large scale melting of aluminium and its alloys. The objective of such processing must be to minimise losses, both from an economic viewpoint and to ensure optimum quality of cast and wrought products. Aluminium losses during melting and casting are primarily due to the formation of dross, a mixture of oxide and melt. Many of the commercially important aluminium alloys contain appreciable levels of magnesium (up to 5%) which can result in enhanced oxidation rates that give rise to particular problems in recycling. Results are presented from a study aimed at reducing melt loss through a knowledge of the mechanism by which dross is formed. Work has centred on an understanding of the early stages in oxide scale growth, a study of growth kinetics and subsequent breakdown of these initial scales to form dross. In humid atmospheres, the amorphous oxide covering both aluminium and aluminium-magnesium at 750°C provides a highly effective barrier protecting the molten metal. In the absence of water vapour, oxide crystal development in aluminium-magnesium alloys is dominated by magnesium, and is extremely rapid in comparison with pure aluminium. Despite the different oxides formed, the manner of crystal formation at the 'amorphous' oxide-melt interface at 750°C on both aluminium and aluminium-magnesium is comparable. Nucleation and growth of crystals in the 'amorphous' film generates high stresses which result in failure of the surface oxide. Scanning electron microscopy has shown that the localised failure of this protective oxide film results in exudations forming on the melt surface, the size and number of which increase with exposure time. These exudations would appear to be the onset of dross formation. Parallel studies of the wetting characteristics of aluminium to alumina have shown that the reported non-wetting is due to the presence of the thin alumina film on the melt surface. Once broken, wetting of the alumina takes place and accounts for the exudation of molten metal through the surface oxide and hence dross formation.